(untitled) (Economic and Political Thought, 2020)
The extremely dynamic development of the Chinese art market, in a broad sense, in recent decades, reflects the growing role of the Chinese economy in the world and the growing wealth of Chinese society. In the years 2008–2011, this market recorded a growth of 500 proc. unprecedented in any other region of the world. In 2018, China’s share in the global art market at 19 proc. confirmed a strong position of this country as one of the top three art markets in the world. At the same time, the Chinese auction market was second in the world. The People’s Republic of China owes its position as a world leader above all to the significant economic reforms of recent years, the effective implementation of the open door policy, and its enormous cultural potential. Chinese culture is a priceless treasure of all mankind, preserved in facilities subject to economic trading. There are few countries that can compete in terms of the wealth of artistic activity with China, one of the biggest states that are a source of cultural property in the world and one of the largest art markets. The purpose of the article is to present the most important issues of the Chinese art market in the last two decades.